Spatial Analysis of Disturbance Gradient in a Forested Landscape of an Indian Central Himalayan Watershed - Sharma, N. K. (Indian Forester, 2005)
In the present study disturbance gradient of Kalsa watershed was analyzed using Remote Sensing and Geographical Information System. A total of ten landuse and vegetation classes were mapped for the area using IRS-ID LISS III data. Disturbance Index map was derived by using fragmentation, patchiness, porosity, interspersion, juxtaposition and biotic zoning (distance from habitation and roads) as input. The disturbance gradient was mapped into four discrete classes' viz., very low, low, medium and high disturbance using geospatial modelling in GIS domain. Disturbance gradient has been compared with all the forest types in the study area.